BIOPHYSICAL METHODS OF STUDY OF PHYTOPLANKTON OF LAKE ISSYK KUL (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
First time the water temperature, underwater irradiance, concentration andphotochemical activity of phytoplankton was investigated with pump and probe method using thesubmersible fluorimeter in south-west region of Issyk-kul lake. Graphs of depth, water temperature,distribution and activity of phytoplankton community were made. The oligotrophic nature of moreparts of Issyk-Kul lake and liability of parts to eutrophication was discovered.
Keywords: phytoplankton, fluorescence, chlorophyll, photosynthesis, anthropogenic pollution.